Development and validation of the caregiver needs and resources assessment - Li, Kin-Kit; Leung, Cyrus L. K.; Yeung, Dannii; Chiu, Marcus Y. L.; Chong, Alice M. L.; Lam, Beck C. Y.; Chung, Edwin K. H.; Lo, T. Wing (Frontiers in Psychology, 2023)
Introduction Existing caregiver assessment tools were long criticized for focusing on the needs and burden while neglecting the importance of the resources. The current study aimed to develop a multidimensional and time-effective assessment tool that measures both needs and resources of non-paid family caregivers of older adults for screening and service-matching purposes. Methods Items of the Caregiver Needs and Resources Assessment (CNRA) were developed from extensive literature reviews and focus group interviews of family caregivers and social workers in the field. In addition, we collected 317 valid responses from family caregivers of older adults from local non-government organizations in examining the psychometric properties of the CNRA. Results The results revealed a 12-factor structure that fitted nicely into the conceptual frame of needs and resources domains. Need factors were positively associated with mental health symptoms, while resource factors were positively associated with peace in mind, meaning-making, and personal gain measures. The 36-item CNRA revealed good internal reliability and convergent validity. Discussion The CNRA has the potential to be used as a compact yet balanced assessment tool for understanding both the needs and resources of caregivers for human service professionals.